AFRIKA TANZT UND SINGT. “Von Tam-Tam zum Jazz”. Compiled and commentated by Rolf Italiaander. 10" LP, Athena 53137 G. Ariola Schallplatten GMBH, Gütersloh, West Germany. - Tracey, Andrew (International Library of African Music, 1961)
pages: 112
Keywords: African Music